Breastfeeding attributable fraction of triple negative breast cancer in the US - Rachel Jaber Chehayeb; Nicole Odzer; Roberta A. Albany; Leah Ferrucci; Daniel Sarpong; Rafael Perez-Escamilla; Jessica B. Lewis; Amanda I. Phipps; Allison Meisner; Lajos Pusztai (npj Breast Cancer)
Abstract Rates of triple negative breast cancer (TNBC) are higher in Black women than in non-Hispanic White women. Breastfeeding duration and younger age at first birth are known risk factors for TNBC and vary by race. To quantify the contribution of these risk factors to disparities in TNBC, we calculated the population-attributable fraction (PAF). A PubMed search was performed to identify relevant studies and pooled odds ratios for breastfeeding for < 6 months and age at first birth < 25 years were calculated. PAF was calculated using the Levin formula. PAF of breastfeeding for < 6 months was 12% (95% confidence interval (CI) 5–20%) among White women and 15% (95%CI 3–26%) among Black women. We estimate that up to 15% of annual new TNBC in Black women and 12% in White women might be avoided by supporting breastfeeding. Policies supporting breastfeeding could hence reduce TNBC incidence and lessen racial disparities.